Gambaran Perilaku Masyarakat dan Keputusan Tidak Menggunakan Gigi Tiruan Lepasan - Kaida, Dita C.; Mintjelungan, Christy N.; Wicaksono, Dinar A. (e-GiGi, 2021)
Abstract: Teeth play an important role in chewing process, speech function, and as an aesthetics for the formation of facial profiles. Problems that often occur in dental and oral health, such as caries which causes tooth decay, therefore, extraction is needed. The solution to tooth loss is to use dentures, however, not everyone wants to do that.Â  There are factors that influence a person's condition in taking action, namely behavior. Health behavior is everything related to one's actions in maintaining and improving one's health. A person's decision to use or not use dentures is influenced by economic factors, knowledge, time, and experience.Thi study was aimed to obtain the community behavior related to the decision not to use removable dentures. This was a literature study using two databases, namely Google Scholar and Digital Reference Garba. Data were analyzed by using a cross sectional study design. The results showed that the community behavior was categorized as good. The community's decision not to use removable dentures was influenced by several factors, namely economy status, knowledge, time, and experience. In conclusion, although the community behavior was categorized as good, there were still many of them who lost their teeth but did not replace their missing teeth with artificial teeth due to a variety of factors.Keywords: behaviour, removable dentureÂ Abstrak: Gigi berperan penting dalam membantu proses pengunyahan, fungsi bicara, dan sebagai estetika pembentukan profil wajah. Masalah kesehatan gigi dan mulut seperti karies menyebabkan rusaknya gigi sehingga perlu pencabutan. Prevalensi penggunaan gigi tiruan tidak sebanding dengan prevalensi kehilangan gigi di masyarakat. Terdapat faktor yang memengaruhi keadaan seseorang dalam melakukan tindakan yaitu perilaku. Pengambilan keputusan seseorang untuk menggunakan atau tidak menggunakan gigi tiruan juga dipengaruhi oleh beberapa faktor yaitu faktor ekonomi, pengetahuan, waktu, dan pengalaman. Penelitian ini bertujuan untuk mengetahui gambaran perilaku masyarakat dan keputusan tidak menggunakan gigi tiruan lepasan. Jenis penelitian ialah literatur reviewe, dengan sumber data diperoleh dari dua database yaitu Google Scholar dan Garba Rujukan Digital kemudian dianalisis dengan desain potong lintang. Hasil penelitian mendapatkan bahwa masih banyak masyarakat yang kehilangan gigi tetapi tidak menggantikan gigi yang hilang dengan gigi tiruan. Gambaran perilaku masayarakat dikategorikan baik dan untuk keputusan masyarakat tidak menggunakan gigi tiruan lepasan dipengaruhi oleh beberapa faktor yaitu faktor ekonomi, pengetahuan, waktu dan pengalaman. Simpulan penelitian ini ialah walaupun gambaran perilaku masayarakat dikategorikan baik namun masih banyak masyarakat kehilangan gigi tetapi tidak menggantikan gigi yang hilang dengan gigi tiruan, yang dipengaruhi oleh berbagai faktor.Kata kunci: perilaku, gigi tiruan lepasan